Evolution on the shoulders of giants: entrepreneurship and firm survival in the German laser industry - Guido Buenstorf (Max Planck Institute of Economics, 2005)
This paper studies 40 years of evolution in the German laser industry to test the generality of evolutionary patterns observed in the U.S. laser industry. Key characteristics found in the U.S. industry are also present in Germany. There is sustained entry into the industry, and neither a shakeout nor first-mover advantages of early entrants are observed. A survival analysis finds that, similar to the U.S. industry, laser firm spin-offs have been systematically more successful than academic startups. Differences in survival and determinants of the spin-off process are traced for alternative kinds of spin-offs, including firms started by serial entrepreneurs.
Keywords: L10; M13; O33; 330; Industry life cycle; submarkets; entrepreneurship; spin-offs; integrating distributors; Unternehmer; Lebenszyklus; Laser; Optoelektronische Industrie; Unternehmensentwicklung; USA; Deutschland